The toll of transition: Caregiver perceptions of family adjustment during the transition off pediatric cancer therapy. Issue 6 (31st January 2022) - Jones, Anna M.; Browne, Emily K.; Adams, Kristen; Potter, Brian S.; McLaughlin Crabtree, Valerie; Jurbergs, Niki; Heidelberg, R. Elyse; Tillery Webster, Rachel
Abstract: Objective: The role of transition‐focused psychology appointments in managing the transition off therapy is unclear. The objective of this research was to explore caregiver perceived familial distress and the role of psychology in preparing families for transition. Methods: Fifty‐seven caregivers of youth, who finished treatment, completed an online questionnaire through a quality improvement project on experiences of families at transition. Twenty‐two percent of caregivers had children who completed a transition‐focused psychology consult and 63% completed a cognitive assessment at transition. Retrospective analyses were conducted assessing the association of psychology visits on caregiver perceptions of being informed of and prepared to manage transition‐related challenges. Results: Most caregivers reported experiencing adjustment concerns for family members. Caregivers of children completing a transition‐focused psychology consult or cognitive assessment reported feeling more informed and greater preparedness to manage difficulties. Although decreased distress was not associated with the visit, those who felt more informed and prepared reported lower distress. Conclusions: Caregivers perceive transitioning off therapy as stressful for their family, though they experience decreased familial distress when informed of and prepared to manage transition‐related challenges. These findings highlight the importance of psychosocial support at transition.